Management and outcome of patients admitted to Charlotte Maxeke Johannesburg Academic Hospital with grade three and four pelvic inflammatory disease - Aldagdag, Najwa Juma (My University, 2021)
Pelvic inflammatory disease (PID) is inflammation of the female upper genital tract and if not treated appropriately can result in serious complications such as chronic pelvic pain, infertility, and ectopic pregnancies. There are multiple risk factors for PID and the most common are young age at sexual intercourse, multiple sexual partners, vaginal douching, and instrumentation of the female genital tract. There have been reports of a higher prevalence of HIV infection in women diagnosed with PID. There is limited literature from South Africa on the diagnosis and management of grade three and four PID. A retrospective study of cases of grade three and four PID, diagnosed in the period from January 2015 to December 2016, was conducted at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). A total of 98 patients were identified, 80 diagnosed with grade three PID and 18 with grade four PID. The proportion of both grade three and four PID was more in HIV-positive patients. The majority of the cases were diagnosed clinically, with ultrasound the most useful, frequently used radiological diagnostic tool. In terms of laboratory investigations, C-reactive protein was a good predictor for the diagnosis of PID. Endogenous gastrointestinal bacteria flora were the most commonly identified causative organisms. Medical management of grade three PID had a high success rate of 72.4%, and the most antibiotics used were a combination of Ampicillin, Metronidazole and Gentamicin. The majority of patients who required surgical intervention had grade four PID, and most of the time fertility-sparing procedures were done. The requirement for second line antibiotics, surgical intervention, relook surgery, and intensive care unit admission was more in HIV-positive patients. A total of two patients died, both HIV-positive and diagnosed with grade four PID, with multidrug resistant bacteria isolated in one of them
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine (Obstetrics and Gynaecology), 2021